2021
DOI: 10.21203/rs.3.rs-812331/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Canine Vector-Borne Diseases of Working Dogs of the Sri Lanka Air Force, Free-Roaming, and Privately-Owned Dogs

Abstract: Background Canine vector-borne diseases (CVBDs) are a significant health problem among dogs globally. The veterinary records show that the military working dogs of Sri Lanka die early at an average age of six years and CVBDs have been listed as one of the speculated causes. This study examined CVBDs in the working dogs of the Sri Lanka Air Force (SLAF) together with free-roaming and privately-owned dogs living close to the SLAF establishments and country-wide. Methods Blood samples were collected from the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Studies aiming to find animal reservoirs found 2 out of 151 dogs (1.32%) positive for Leishmania amastigotes [ 5 ], rK39 positivity in 1 out of 114 dogs (0.87%) [ 6 ], and in 4 out of 51 (7.8%) dogs in another study [ 7 ]. A more recent survey among 668 dogs in 18 out of 25 districts in Sri Lanka revealed a Leishmania amastigote prevalence of only 0.9% (2/668) in blood [ 9 ]. These findings suggest the possibility of dogs acting as reservoir hosts [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies aiming to find animal reservoirs found 2 out of 151 dogs (1.32%) positive for Leishmania amastigotes [ 5 ], rK39 positivity in 1 out of 114 dogs (0.87%) [ 6 ], and in 4 out of 51 (7.8%) dogs in another study [ 7 ]. A more recent survey among 668 dogs in 18 out of 25 districts in Sri Lanka revealed a Leishmania amastigote prevalence of only 0.9% (2/668) in blood [ 9 ]. These findings suggest the possibility of dogs acting as reservoir hosts [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%